NLFEA of Reinforced Concrete Corbels: Proposed Framework, Sensibility Study, and Precision Level - Luan Reginato; Alex M. D. de Sousa; João V. C. Santos; Mounir K. El Debs (Buildings, 2023)
Non-linear finite element analysis (NLFEA) has been frequently used to assess the ultimate capacity of reinforced concrete (RC) structures under the most complex conditions. Nevertheless, the guidelines using such methods to evaluate RC corbels are limited. In addition, the influence of material modeling options regarding the behavior of such members was not investigated until now. This paper proposes to present a framework for the NLFEAs of RC corbels using the Concrete Damaged Plasticity (CDP) model. the influence of several modeling choices related to this constitutive model also is discussed in detail, including the assumed stress–strain behavior in compression and tension and the parameters related to the yield criterion and flow rule. For this, a first set of test results was used to validate the proposed approach to the NLFEA. Afterwards, the sensibility of the numerical results for several modeling choices was investigated. In the end, the proposed framework for the NLFEA was checked against a database of 36 test results from the literature. The mean ratio between the predicted and experimental test results was 1.015 with a coefficient of variation of only 8.57%. The governing failure mechanism of the tests was predicted correctly in approximately 88% of the simulations. In summary, the proposed approach allows for predicting the ultimate capacity and failure mechanism of RC corbels accurately.